2013
DOI: 10.2478/v10220-012-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine as a Feed Supplement for Piglets: a Review / Glutamina jako dodatek do paszy dla prosiąt: przegląd

Abstract: Weaning is a crucial moment in a piglet’s life. It is characterized by a generally low nutrient intake and adverse changes in the small intestinal mucosa. Proper feeding is therefore necessary to ensure normal development of the gastrointestinal tract. One substance that could provide intestinal epithelial cells with necessary energy is the amino acid glutamine. It improves epithelium structure and accelerates the growth of intestinal villi in which nutrients are absorbed, thus improving feed utilization and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 181 publications
0
5
0
Order By: Relevance
“…Feeding diets supplemented with 0.4% Gln, Arg or their combination to does and rabbits did not affect animal performance. Studies in piglets have shown that there is not always a productive enhancement with Gln supplementation despite the well reported positive effects of Gln on gut integrity and physiology [26]. In previous research, we were unable to detect significant differences on feed efficiency, daily gain or feed intake in young rabbits fed diets supplemented with 1% Gln [12].…”
Section: Discussionmentioning
confidence: 76%
“…Feeding diets supplemented with 0.4% Gln, Arg or their combination to does and rabbits did not affect animal performance. Studies in piglets have shown that there is not always a productive enhancement with Gln supplementation despite the well reported positive effects of Gln on gut integrity and physiology [26]. In previous research, we were unable to detect significant differences on feed efficiency, daily gain or feed intake in young rabbits fed diets supplemented with 1% Gln [12].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, it is very important to add nutrients during weaning. Glutamine can be effectively used in the small intestine and can repair intestinal mucosal damage caused by weaning stress [ 18 ]. Glutamine is the main source of intestinal cells; in fact, glutamate and aspartic acid can also be used as fuel to provide energy to the intestine and so does glutamine [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is also a precursor to glutathione, which is an essential antioxidant protecting cells from free oxygen radicals. Positive effects were obtained when feeding 1% glutamine in feed to 21-day-old weaned piglets for 20 days (Hanczakowska and Niwinska 2013).…”
Section: Glutamine Glutamate and Aspartatementioning
confidence: 99%
“…There are several mechanisms by which glutamine and glutamate can contribute to healthy gut development in weaned piglets (Xiong et al 2019). Both of them are important sources of energy for intestinal epithelial cell proliferation and integrity repair (Hanczakowska and Niwinska 2013;He et al 2016b) and both serve as oxidative substrates for intestinal epithelial cells and are important sources of carbon atoms for gluconeogenesis (Modina et al https://doi.org/10.17221/72/2023-VETMED 2019). In the intestine, glutamine may increase secretory IgA production by regulating the intestinal microbiota and/or T-cell-dependent and T-cellindependent pathways (Wu et al 2016).…”
Section: Practical Use Of Glutamine In Weaned Pigletsmentioning
confidence: 99%